'Rubbery' ASEAN: mediating people-movement in Southeast Asia. (24th September 2019) - Quayle, Linda
Southeast Asians on the move are caught 'between a fluid region and a hard state', as Malaysian historian Farish Noor puts it. Drawing on mobilities theory, this article seeks to locate the Association of Southeast Asian Nations (ASEAN) within this ideational map of flows and gates, arguing that it can best be characterised as a 'semi-soft' entity, mediating between the need for mobility and the fear of mobility. ASEAN intersects with people-movement in the areas of skilled and unskilled labour; connectivity and development; and security and protection. On aggregate, its goals reflect an ambivalence that leaves it open to charges of ineffectiveness, even duplicity. Yet this incoherence might be both an inevitable and also sometimes positive element of ASEAN's shock-absorber role, as it both buffers and is imprinted by the dual pressures of fluidity and fixity.